Cell image reconstruction using digital holography with an improved GS algorithm - Jiang, Yuhao; Li, Hongzhong; Pang, Yu; Ling, Jiwei; Wang, Hao; Yang, Yuling; Li, Xinyu; Tian, Yin; Wang, Xiuxin (Frontiers in Physiology, 2022)
Digital holography is an effective technology in image reconstruction as amplitude and phase information of cells can be acquired without any staining. In this paper, we propose a holographic technique with an improved Gerchberg-Saxton (GS) algorithm to reconstruct cell imaging based on phase retrieval information. Comparative experiments are conducted on four specific models to investigate the effectiveness of the proposed method. The morphological parameters (such as shape, volume and sphericity) of abnormal erythrocytes can be obtained by reconstructing cell hologram of urinary sediment. Notably, abnormal red blood cells can also be detected in mussy circumstances by the proposed method, owing to the significantly biophysical contrast (refractive index distribution and mass density) between two different cells. Therefore, this proposed method has a broad application prospect in cell image reconstruction and cell dynamic detection.